PENGARUH KENAIKAN TARIF PPN TERHADAP PENJUALAN PADA PT GRUTI LESTARI PRATAMA - Susilawati; Nasution, Frida Yasmine (Jurnal Budgeting, 2025)
ABSTRACT . This study aims to determine whether there is an effect of increasing the Value Added Tax rate from 10% to 11% on sales. The data used is qualitative data in the form of interview results with the Head of Taxation at PT Gruti Lestari Pratama and sales data from October 2021 to December 2022. The data collection techniques used were interviews and documentation. The collected data were then processed using the t-test and analyzed using the descriptive analysis method. The results of the research and discussion that have been conducted indicate that the factors that influence the sales of PT Gruti Lestari Pratama are government policies in this case including tax rates, global economic conditions that can affect prices and demand, socio-economic changes in society, intense competitive environment, company production capacity and appropriate and competitive pricing policies. There is a difference in sales levels before and after the increase in VAT rates.